A Survey on Ethical Hacking Techniques - Sathya, J; Manivannan, T (International Journal of Computer Sciences and Engineering, 2025)
Hacking is a task in which, a person utilize the weakness in a system for self-profit or indulgence. Ethical hacking is an indistinguishable activity which aims to find and rectify the weakness in a system. In the growing era of internet computer security is of utmost concern for the organizations and government. These companies are using Internet in their wide variety of applications such as marketing, electronic commerce, and database access. But at the same time, data and network security is a serious issue that has to be talked about. This paper attempts to discuss the overview of hacking and how ethical hacking disturbs the security. Also the Ethical Hackers and Malicious Hackers are different from each other and playing their important roles in security. This paper studied the different types of hacking with its phases. The hacking can also be categorized majorly in three categories such as white hat, black hat and grey hat hacking. This paper also presents a comparison of the hacking categories with different methods of penetration testing